Changes in Post-prandial Glucose and Pancreatic Hormones, and Steady-State Insulin and Free Fatty Acids after Gastric Bypass Surgery - Campos, Guilherme M. (2013)
BACKGROUND: Changes in the multiple mechanisms that regulate glucose metabolism after gastric bypass (RYGB) are still being unveiled. OBJECTIVE: To compare the changes of glucose and pancreatic hormones [C-peptide, glucagon and pancreatic polypeptide (PP)] during a meal test (MTT) and steady-state insulin and free fatty acid (FFA) concentrations during euglycemic–hyperinsulinemic clamp 14 days and 6 months after RYGB in morbidly obese non-diabetic patients. SETTING: Academic Medical Center, United States. METHODS: Two groups were studied at baseline and at 14 days: RYGB followed by caloric restriction (RYGB, n=12) or equivalent caloric restriction alone (Diet, n=10), to control for energy intake and weight loss. The RYGB group was studied again at 6 months, to assess the changes after substantial weight loss. During MTT we determined the early and overall changes in glucose and pancreatic hormone concentrations, and during the clamp we assessed steady-state insulin and FFA concentrations. RESULTS: After 14 days, RYGB subjects had enhanced post-prandial glucose, C-peptide and glucagon responses and decreased post-prandial PP concentrations. Steady-state insulin concentrations were decreased at 14 days only in RYGB subjects, and FFA increased in both groups. Six months after RYGB and substantial weight loss, the decrease in insulin concentrations during clamp persisted, and there were further changes in post-prandial glucose and glucagon responses. FFA concentrations during clamp were significantly lower at 6 months, relative to pre-surgical values. CONCLUSIONS: RYGB produces, in morbidly obese non-diabetic patients, early changes in post-meal glucose, C-peptide, glucagon and PP responses, and appears to enhance insulin clearance early after RYGB and improve insulin sensitivity in adipose tissue at 6 months post-surgery. The early changes cannot be explained by caloric restriction alone.